Implementasi Metode Modernisasi Cassava Product dan Zero Waste Management Pada UKM Keripik Singkong di Desa Karangduren Kab Semarang - Umi Fatmawati; Dewi Puspita Sari; Erma Kumala Sari (Universitas Sebelas Maret, 2021)
Cassava chips are one of the favorite snacks of various people who are cheap. The cassava chips home industry in Karangduren Village, Tengaran District, Semarang Regency revealed that there are still many problems related to the production, packaging, marketing, and waste processing processes that affect the quality of chips and reduce partner income. The objectives of this service activity are 1). Improving the quality of the process and product of cassava chips which are preferred in the community to increase the income of the owner, 2). Assisting the home industry of chips in managing waste to increase the environmental aesthetics and provide added value. The methods implemented in this service activity are 1. Introduction of an oil draining machine and assistance in developing chip products 2. Improvement of production process facilities. 3. Training the employee on the use of animal feed and making compost from waste banana peels and cassava. The result of this activity is that several new product variants have been produced with a better taste and appearance of the packaging, such as cassava hot chips, cassava cheese, cassava leaf chips, a more hygienic and standardized environment for producing chips, as well as by-products from waste treatment. such as animal feed and compost.